Determinants of depression in primary caregivers of disabled older relatives: a path analysis. Issue 1 (December 2017) - del -Pino-Casado, Rafael; Palomino-Moral, Pedro; Pastor-Bravo, Maria del Mar; Frías-Osuna, Antonio
Abstract Background Despite the large literature analysing factors related to depression, several factors such as caregiving obligation and the interrelationships among the different variables relating to depression have been little studied. The current study aimed to analyse the effect of caregiving obligation (beliefs regarding obligation and social pressure) on depression, and the mediating effects of perceived burden on the relationship between stressors and depression, in primary caregivers of older relatives. Methods Cross-sectional study design. A probabilistic sample of caregivers from Spain (N = 200) was used. The data collection was conducted in 2013 through structured interviews in the caregivers' homes. The measures included sense of obligation for caregiving, perceived burden, stressors and depression. Results Depression had a direct and positive association with perceived burden, behavioural problems, and social pressure, and it was indirectly related through perceived burden to behavioural problems, independence for the activities of daily living and beliefs of obligation. Conclusions Our results support the multidimensional concept of obligation, suggesting the existence of both an external obligation (social pressure) and an internal obligation (beliefs of obligation); (b) our findings support the hypothesis that external obligation is related to negative caregiving consequences, while internal obligation protects from these consequences; and (c) our findings support the partial mediation of stressors on depression by perceived burden. The relevance of the research to clinical practice includes the importance of understanding the perceived obligation of caregiving related to both internal and external sources of obligation.